2020
DOI: 10.2147/cmar.s257299
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prognostic Significance of PD-L1 Expression and Its Tumor-Intrinsic Functions in Hypopharyngeal Squamous Cell Carcinoma</p>

Abstract: The expression of programmed death-ligand 1 (PD-L1) is common in various solid human cancers and it is an important therapeutic target. However, the expression pattern, clinical significance and potential mechanism of PD-L1 in hypopharyngeal squamous cell carcinoma (HSCC) are still lacking. Methods: PD-L1 expression in HSCC tumor tissues and paired adjacent hypopharyngeal mucosal tissues was detected using immunohistochemistry assay, and the clinical significance of PD-L1 in HSCC was characterized. In vitro as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 42 publications
2
21
0
1
Order By: Relevance
“…23,24 Second, the predictive Recently, studies have shown that gene patterns, PD-L1, and the immune microenvironment can also reflect the prognosis of HSCC. [25][26][27] Thus, a multi-omics model should be developed in the future to improve the predictive accuracy of prognosis in these patients. Third, the present nomogram was developed based on a retrospective population-based analysis, which was not externally validated.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Second, the predictive Recently, studies have shown that gene patterns, PD-L1, and the immune microenvironment can also reflect the prognosis of HSCC. [25][26][27] Thus, a multi-omics model should be developed in the future to improve the predictive accuracy of prognosis in these patients. Third, the present nomogram was developed based on a retrospective population-based analysis, which was not externally validated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since PD-L1 is often reported to be overexpressed in malignant tumors, mechanically, helps cancer cells evade recognition by the host immune system, PD-L1 has also become the focus of oncologic research (26,27). Previous studies have reported the immunopathogenic effect and cancer-intrinsic function of PD-L1 in HSCC (11,28), however, in general, the contributions of PD-L1 in the pathogenesis still need more discussion. In this study, we found that knockdown of HOXA11-AS1 suppressed immune escape and metastasis in HSCC through down-regulating PD-L1 levels by inhibiting the interaction between FOSL1 and PTBP1.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wintterle et al suggested that PD-L1 modulated CD4+ and CD8+ T cell levels by increasing cytokine concentration, such as IFN-γ, thus showing immunomodulatory function in glioma cells (9). Similarly, the high expression of PD-L1 facilitated HSCC cells to escape recognition of the host immune system and accelerated the tumor metastasis (10,11), indicating that the inhibition of PD-L1 might has positive effect for HSCC treatment. However, the speci c function mechanism of PD-L1 needs more investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis demonstrated that PD-L1 expression was high in hypopharyngeal carcinoma. There are data to suggest that overexpression of PD-L1 can act as a significant biomarker for the adverse clinicopathologic features and poor prognosis of patients with hypopharyngeal squamous cell carcinoma [ 25 ]. Our study reported that PD-L1 expression was high in three out of four patients with laryngeal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%